Study of policy determination to create a healthy watershed: A case study of Lepan watershed in Langkat district, North Sumatera, Indonesia - Faisal Ridho; Samsuri; Affifuddin, Yunus (Journal of Sylva Indonesiana, 2022)
Lepan watershed has declined in function over the past two decades. One of the contributing factors is unsustainable forest management and low public awareness in maintaining an ecosystem. Upstream damage occurs due to illegal logging and deforestation for agricultural purposes or exploitation of forest products. Meanwhile, the conversion of forest land into commercial or residential use occurs in the middle to downstream areas. The research used a descriptive analysis method based on Situation, Structure, Behavior, Performance (SSBP), and Analytical Hierarchy Process (AHP) method with data processing using the Expert Choice software. Research shows that the government's percentage of performance related to policies that have been implemented in the Lepan watershed is considered reasonable by the community, with a value reaching 62%. Alternatives in providing of Lepan watershed being healthy is returning of function by value weight 5.6, conservation by value weight 3.4, and planting by value weight 2.1